Methodologies for Modeling of Solidification Microstructure and Their Capabilities - Stefanescu, Doru M. (ISIJ International, 1995)
During the last decade, solidification modeling has known a sustained development effort, supported by academic as well as industrial research. The driving force behind this undertaking was the promise of predictive capabilities that will allow process and material improvement. The most significant recent rogress has been incorporation of transformation kinetics, for both the liquid/solid and the solid/solid transformation, in the macro-transport models. The results of these efforts have materialized in a proliferation of publications and commercial software, some of which have penetrated the industry. Numerous claims are made regarding modeling methods accuracy and capabilities. They include prediction of casting defects, of microstructure length scale and composition, and even of mechanical properties. A reality test of these claims is the subject of the present paper. The methodologies for macro transport-transformation kinetics modeling (MT-TK), and therefore for prediction of microstructural evolution, can be broadly classified as being based on the continuum approach (deterministic), or on the stochastic (probabilistic) approach, or, more recently, on a combined approach. Originally the MT-TK analysis was performed for the liquid/solid transformation. Subsequently, it has been extended to the solid/solid transformation, thus resulting in prediction of room temperature microstructure. Specifically, it has been attempted to predict features like microsegregation, microstructure length scale, fraction of phases, structural transitions, hardness, microhardness, and tensile properties. The success of these efforts is critically reviewed in the paper.